2010
DOI: 10.1038/nchem.859
|View full text |Cite
|
Sign up to set email alerts
|

Anion-switchable supramolecular gels for controlling pharmaceutical crystal growth

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
262
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 281 publications
(268 citation statements)
references
References 50 publications
5
262
0
1
Order By: Relevance
“…The gelator was then removed by 30 washing the samples with hot methanol in a Soxhlet apparatus for up to three days. Removal of the gelator was confirmed by both chemical analysis which showed no nitrogen in the washed samples from either gelator or initiator, and by NMR spectroscopy of extracts from polymer samples immersed in DMSO-d 6 for 35 several hours which showed no signals corresponding to gelator.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The gelator was then removed by 30 washing the samples with hot methanol in a Soxhlet apparatus for up to three days. Removal of the gelator was confirmed by both chemical analysis which showed no nitrogen in the washed samples from either gelator or initiator, and by NMR spectroscopy of extracts from polymer samples immersed in DMSO-d 6 for 35 several hours which showed no signals corresponding to gelator.…”
Section: Resultsmentioning
confidence: 99%
“…The present study utilises two hexylene spaced bis-urea gelators functionalised with either alanine or phenylalanine derived end groups, namely 1 and 2 respectively (Scheme 1). 30,31 The compounds gel a variety of solvents including a 1:1 mixture of polymer precursor methyl methacrylate (MMA) and cross-linker 5 ethylene glycol dimethacrylate (EGDMA). Electron microscopy revealed that the mesoscopic morphology of the gels is different for the two compounds with xerogels of 2 showing small cylindrical fibres whilst 1 consists of two-dimensional ribbon-like structures ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 A typical 50 procedure comprises warming a solution of gelator and drug substance in a compatible solvent to give a homogeneous solution and allowing the mixture to cool. The gelation and crystallization processes are orthogonal and generally time-resolved with gelation occurring over a period of minutes followed by 55 crystallization over a period of hours to days.…”
Section: Crystallization In Low Molecular Weight Supramolecular Gelsmentioning
confidence: 99%
“…13 In contrast, anions, particularly strong hydrogen bond acceptors such as chloride and acetate, tend to 'turn off' gelation by competitive hydrogen bonding to the urea NH groups. 19,20 Indeed reports of anion-promoted gelation are very rare. 21,22 We anticipate that changing from pyridyl ureas to simple pyridinylmethyl ureas (Scheme 1) should radically change the aggregation behaviour of the urea since the introduction of a methylene spacer between the urea and heterocycle means that the oxygen acceptor is no longer sterically hindered, hence markedly favouring urea···urea hydrogen bonding via the 2 1 (6) urea -tape motif.…”
mentioning
confidence: 99%